The time traveler's wife - Niffenegger, Audrey (Orlando : Harcourt, 2003)
On the surface, Henry and Clare Detamble are a normal couple living in Chicago's Lincoln Park neighborhood. Henry works at the Newberry Library and Clare creates abstract paper art, but the cruel reality is that Henry is a prisoner of time. It sweeps him back and forth at its leisure, from the present to the past, with no regard for where he is or what he is doing. It drops him naked and vulnerable into another decade, wearing an age-appropriate face. In fact, it's not unusual for Henry to run into the other Henry and help him out of a jam. Sound unusual? Imagine Clare Detamble's astonishment at seeing Henry dropped stark naked into her parents' meadow when she was only six. Though, of course, until she came of age, Henry was always the perfect gentleman and gave young Clare nothing but his friendship as he dropped in and out of her life. It's no wonder that the film rights to this hip and urban love story have been acquired.
"Harvest reading guide"--P. [4] of cover.
Keywords: Librarians -- Fiction; Time travel -- Fiction; Married people -- Fiction; Women art students -- Fiction; Domestic fiction; Fantasy fiction